Hubungan Akses Media Sosial Remaja Terhadap Perilaku Seks Remaja Kelas XI di SMA Barunawati Surabaya - Dedi Irawandi; Dya Sustrami (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2019)
Many factors affect teenage sexual behavior including access to social media. The purpose of this study was to determine the relationship between adolescent social media access to adolescent sexual behavior class XI in SMA Barunawati Surabaya. The study design uses observational analytic cross-sectional approach. The population of the study was 214 respondents, a sample of 140 respondents. The instrument used was a questionnaire sheet. Data analysis used Chi-Square test Î± <0.05. Statistical test results obtained access to adolescent social media with adolescent sexual behavior Ï = 0.035 (Î± <0.05). There is a relationship between adolescent social media access with adolescent sexual behavior. Peer group with adolescent sexual behavior Ï = 0.032 (Î± <0.05). There is a relationship between teenage sexual behavior. The implications of this research are the need for close monitoring or supervision of parents about the frequency of children accessing social media, providing education about the dangers of adolescent sexual behavior and monitoring children's relationships. It is recommended for teachers in schools to help in providing education about the dangers of teenage sexual behavior.Keywords: access to adolescent social media, peer groups, adolescent sexual behavior